Muscle strength and ACL injury in Portuguese female handball players - Estriga, M. L; Marques de Carvalho, J.; Bernandez, J.; Massada, L. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Purposes: to investigate the relation between the maturation, muscle strength and ACL injury risk. Total sample: 496 Portuguese female handball players. We measured some isokinetic muscular force indicators and vertical jump capacity in the various subgroups and accounted for all previous and subsequent ACL injuries. Conclusions: our results reinforce the importance of the knee flexor musculature in the ACL rupture prevention.